Financial accountability on local government and regional economic growth - Fitra Dharma (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Audit opinions should be linked to regional economic growth as evidence of financial accountability. Previous research in Indonesia on government spending and regional economic growth has been inconsistent. Audit opinion of local government financial statements could result in discrepancies in the research findings. The purpose of this study is to determine whether there is higher economic growth in local governments that obtain an unqualified audit opinion (UAO) compared to local governments that obtain a modified audit opinion (MAO). This study uses district and city governments in Indonesia from 2016 to 2020 as a sample. The Mann-Whitney test shows that local governments that receive an unqualified audit opinion (UAO) have higher economic growth than those that receive a modified audit opinion. The results of this study show empirically that local government financial accountability is associated with regional economic growth.